Incomplete recovery of takotsubo cardiomyopathy is a major determinant of cardiovascular mortality. (25th November 2020) - Matsushita, K; Lachmet-Thebaud, L; Marchandot, B; Sato, C; Dagrenat, C; Greciano, S; De Poli, F; Leddet, P; Trimaille, A; Heger, J; Reydel, A; Trinh, A; et al.
Abstract: Introduction: Although there is an apparent rapid and spontaneous recovery of left ventricular ejection fraction (LVEF) in patients with takotsubo cardiomyopathy, recent studies have demonstrated the long-lasting functional impairment in those patients. Purpose: We sought to evaluate the predictors of incomplete recovery in chronic phase and its impact on cardiovascular mortality after takotsubo cardiomyopathy. Methods: Patients with takotsubo cardiomyopathy between 2008 and 2018 were retrospectively enrolled in three different institutions. Takotsubo cardiomyopathy was diagnosed according to the European Society of Cardiology Heart Failure Association criteria. After exclusion of in-hospital deaths, 407 patients were split into 2 subgroups according whether their LVEF were >50% (recovery group; n=333), or ≤50% (incomplete recovery group; n=74) at follow-up. The primary endpoint was the impact of incomplete recovery on cardiovascular mortality. Results: Patients with incomplete recovery were more likely to be male, to have dementia, pacemaker, and supraventricular arrhythmia. C-reactive protein (CRP) levels on admission, at peak, and at discharge were significantly higher in patients with incomplete recovery. By multivariate logistic regression analysis, lower EF at discharge (odds ratio [OR]: 0.91; 95% confidence interval [CI]: 0.88 to 0.95; p<0.001) and higher CRP levels (OR: 5.56; 95% CI: 1.86 to 16.61; p<0.001) were independent predictors of incomplete recovery at follow-up. The cumulative event-free survival rate according to cardiovascular death was significantly lower in the incomplete recovery group (p<0.001; log-rank test). Conclusions: We demonstrate that incomplete recovery after takotsubo cardiomyopathy is characterized by a residual systemic inflammation and an increased cardiac mortality at follow-up. Altogether, our findings underline patients with persistent inflammation as a high-risk subgroup, to target in future clinical trials with specific therapies to attenuate inflammation. Funding Acknowledgement: Type of funding source: None